Postreperfusion syndrome in liver transplantation: Outcomes, predictors, and application for recipient selection. Issue 4 (19th January 2022) - Bekki, Yuki; Myers, Bryan; Wang, Ryan; Smith, Natalie; Zerillo, Jeron; Rocha, Chiara; Tabrizian, Parissa; Moon, Jang; Arvelakis, Antonios; Facciuto, Marcelo E.; DeMaria, Samuel; Florman, Sander
Abstract: Background: This study aimed to identify risk factors for postreperfusion syndrome (PRS) and its impact on LT outcomes. Methods: Data analysis was performed in 1021 adult patients undergoing donation after brain death (DBD) LT to identify PRS incidence, the risk factors for PRS development, and its impact on LT outcomes. Results: The overall incidence of PRS was 16.1%. Independent risk factors for PRS included donor age (odds ratio (OR) 1.01, P  = .02), donor body mass index (BMI) (OR 1.04, P  = .003), moderate macrosteatosis (OR 2.48, P  = .02), and cold ischemia time (CIT) (OR 1.06, P  = .02). On multivariable analysis for 30‐day graft failure, PRS (hazard ratio (HR) 3.49; P  < .001) and Model for End‐stage Liver Disease (MELD) score (HR 1.01; P  = .05) were independent risk factors. Patients were categorized into four distinct groups based on PRS risk groups and MELD groups, which showed different 1‐year graft survival ( P  < .001). There were comparable outcomes between low PRS risk ‐ high MELD and high PRS risk ‐ low MELD group ( P  = .33). Conclusions: Donor age, donor BMI, moderate macrosteatosis, and CIT were identified as risk factors for the development of PRS in LT using DBD grafts. PRS risk evaluation may improve donor‐to‐recipient matching based on their MELD scores.